Changes in placental elastography in the third trimester - Analysis using a linear mixed effect model. (October 2021) - Edwards, Christopher; Cavanagh, Erika; Kumar, Sailesh; Clifton, Vicki L.; Borg, Danielle J.; Priddle, Jacob; Wille, Marie-Luise; Drovandi, Christopher; Fontanarosa, Davide
Abstract: Introduction: Research into the role of ultrasound elastography to assess compromised placental tissue is ongoing. There is particular interest in evaluating its potential in the investigation of changes associated with uteroplacental dysfunction. To date, there is limited data on how different maternal and fetal considerations, such as advancing gestational age, amniotic fluid Index (AFI) and maternal body mass index (BMI) may influence shear wave velocity (SWV) measurements. This study aimed to evaluate longitudinal changes in SWV throughout gestation and model these changes with other developing fetal and maternal physiological and biological characteristics. Methods: The study utilised 238 singleton pregnancies and collected longitudinal data at repeated intervals in the 3rd trimester representing 629 individual data points. Linear mixed model regression analysis was used to identify significant predictors for SWV. Results: From a total of ten variables selected for modelling, only gestational age, AFI, BMI, and sample depth were found to be significant predictors of placental SWV, and gestational age and AFI were found to have only a minimal impact on SWV. Discussion: Sophisticated statistical modelling demonstrates that many of the expected maternal and fetal changes in the 3rd trimester have no or minimal impact on placental SWV. Understanding which factors influence placental SWV is essential to ascertain the technique's utility in managing pregnancies complicated by placental dysfunction in the future. Highlights: Ultrasound elastography can be applied to the placenta to measure stiffness. Modelling demonstrated minimal or no impact of many maternal and fetal parameters on placental stiffness. Elastography acquisition techniques should be optimised for reliable measurements. The comprehensive longitudinal analysis will support future research of elastography and placenta dysfunction.